Promoting Eco-innovations to Leverage Sustainable Development of Eco-industry and Green Growth - Sarkar, A.N. (European Journal of Sustainable Development, 2013)
In the modern world, ecologyand the economy are on cross roads. With the increasingpace of globalization and economic liberalization, giving birth to the rapid growth ofconsumerism by the modern civilization,there is growing consciousness to movegradually towards green growth with sustainability. This is now becoming possible byenhancing eco-consciousness both among theproducers as well as the consumers. Thechosen path is obviously to go in for more and more eco-innovations to providecomplementarily to industrialproduction without sacrificing much on the production aswell as economic front. Renewable alternate technologies – widely known as eco-technologies, are now being developed withmassive investment on R&D activities byseveral research organizations across the world to achieve this mission. To leverage thegains from eco-innovations and achievedthrough proactive and carefully plannedorganizational and R&D support, there seems to be a surge in the growth of Eco-industries; which in turn, are getting increasingly organized asa chain of eco-industry, byconstantly evolving replicableas well as sustainable eco-industrial models in the emergingsectors of economy, prominently in the EU countries.The paper takes a holistic and strategic review on how the Eco-innovations and their eco-specific promotional and developmental efforts are stimulating the sustainabledevelopment of Eco-industriesand enhancing Green growth bysetting up of demonstrableEco-industrial models in multi-sectoral areas in Europe and the other parts of the world.The paper also provides a brief account of various corporate and entrepreneur initiativestaken in developing sustainable Eco-industrial business models and the methodologies tomeasure the impact of eco-innovation projects.